2012
DOI: 10.1186/1471-2407-12-310
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genome-wide expression profiling identifies three distinct molecular subgroups of renal cell carcinoma with different patient outcome

Abstract: BackgroundRenal cell carcinoma (RCC) is characterized by a number of diverse molecular aberrations that differ among individuals. Recent approaches to molecularly classify RCC were based on clinical, pathological as well as on single molecular parameters. As a consequence, gene expression patterns reflecting the sum of genetic aberrations in individual tumors may not have been recognized. In an attempt to uncover such molecular features in RCC, we used a novel, unbiased and integrative approach.MethodsWe integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…5A). CD27 and CD70 gene expression obtained from a recent DNA-microarray analysis (20) confirmed this finding (Fig. 5B).…”
Section: Preferential Infiltration Of Cd27supporting
confidence: 78%
See 2 more Smart Citations
“…5A). CD27 and CD70 gene expression obtained from a recent DNA-microarray analysis (20) confirmed this finding (Fig. 5B).…”
Section: Preferential Infiltration Of Cd27supporting
confidence: 78%
“…Gene expression data of 116 RCCs and six normal kidneys were obtained from a recently published microarray study (20). Microarray data are available in Gene Expression Omnibus under GSE19949.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…S7A). Even more importantly, aneuploidy levels, expressed as the variance of chromosome copy numbers from SNP data (31), correlate linearly with miR-28-5p expression levels in ccRCC stratified by grade ( Fig. 7D and Supplementary Fig.…”
Section: A B C D E Fmentioning
confidence: 93%
“…An example showing hierarchical clustering of genes in ccRCC and pRCC (Beleut et al 2012) is shown in Fig. 4.…”
Section: Dna Microarrays For Screening Rcc-specific Marker Expressionmentioning
confidence: 99%